The intentional relationship occupational therapy and use of self - Taylor, Renée R. 1970- (Philadelphia F.A. Davis Company, 2020)
The contents of this book are aimed at practitioners' expressions of the dilemmas and challenges they face in therapeutic use of self, as well as their descriptions of the way they attempt to manage these circumstances. Additionally, I decided to look for instances of excellence in therapeutic use of self in occupational therapy that could be shared with practicing occupational therapists, occupational therapy assistants, educators, fieldwork supervisors, and students of occupational therapy. This edition provides more detail about mode use, including recommended body language, questions, and comments that are reflective of each mode. The reader will also find deeper and more critical discussion of suboptimal communication in therapy and what therapists can do to minimize it, and an emphasis on understanding and managing difficult behavior and resolving empathic breaks and conflicts"--
Includes bibliographical references and index.
Keywords: Self Concept; Intention; Professional-Patient Relations; Occupational Therapy -- methods